Peramalan Strategi Pelanggan serta Perpindahan Pelanggan Indomaret dan Alfamart dengan Metode Game Theory dan Markov Chain - Muhammad Aliwafa; Sukanta Sukanta; Rianita Puspa Sari (Jurnal Serambi Engineering, 2021)
Karawang is one of the areas that developed into one of the largest industrial cities in Indonesia. Karawang experienced rapid growth, especially in the industrial and commercial sectors. This has led to the occurrence of the change of the pattern of life in the community, so that modern society become identical with a consumptive lifestyle. Leads to the new needs that actually put forward in public life, one of which is the demand needs of life, especially basic needs. That's what became the basis of the number of franchise mini market opened, but there are two big names that are often visited by the people that Indomaret and Alfamart. The purpose of this study is to analyze the probability of the displacement of the consumer between two mini market. The method of game theory used for the analysis of customer strategy of the two-mini market, while the Markov chain is used to analyze the displacement of the customer. Results from game theory such Alfamart winning strategy on price and Indomaret winning strategy on the completeness of the product. While the results from the Markov chain there is a movement of consumers from Indomaret to Alfamart.